Teaching Creativity of Practising Programme Teachers Islamic Religious Education Programme - Rizki, Agam Muhammad; Husnizar, Husnizar; Maitrianti, Cut (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. A teacher must have superior creativity in the learning process in the classroom because the progress of student learning also depends on the creativity of the teacher in teaching. Teachers who have high creativity will be able to stimulate students to love the subject matter they deliver. Teachers' creativity in teaching can make learning fun. Purpose. The purpose of this research is to find out the teaching creativity that arises from the Islamic Religious Education study programme practicing teachers in carrying out learning and the supporting and inhibiting factors of teaching creativity of Islamic Religious Education study programme practicing teachers in carrying out learning. Teaching creativity is an effort to utilise something new. Method. This research method uses mixed methods, namely a combination of qualitative and quantitative. The data collection technique was obtained through interviews, observation and documentation. Results. The results showed that the teaching creativity that emerged from the practicing teachers of the Islamic Religious Education Study Program in carrying out the learning that emerged was 49.33% for creativity in designing lesson plans (less), 45% for the realisation of lesson plan design (very less) and 46.15% for the attitude that emerged during teaching (less). Conclusion. The conclusion of this study is that the supporting factors of teaching creativity of practicing teachers of Islamic Education Study Program in implementing learning are the family, school and community environment. While the inhibiting factors of teaching creativity of practicing teachers of Islamic Education Study Program in implementing learning are age, strong will, class and time management, teacher resources and understanding, facilities and infrastructure, and parental support for students in learning.